Pengaruh Current Ratio (CR) Dan Net Profit Margin (NPM) Terhadap Harga Saham Melalui Earning Per Share (EPS) Sebagai Variabel Intervening Pada Perusahaan Pertambangan - Intafullaili, Bilgis Nisa'; Sriyono, Sriyono; Kumala Sari, Herlinda Maya (Universitas Muhammadiyah Pontianak, 2025)
This study aims to analyze the impact of the Current Ratio (CR) and Net Profit Margin (NPM) on stock prices with Earnings Per Share (EPS) as an intervening variable in mining companies. This research employs a descriptive quantitative approach using panel data and purposive sampling techniques. The findings indicate that CR affects EPS but not significantly, while NPM has no significant impact on EPS. Additionally, CR does not significantly influence stock prices, whereas NPM and EPS have significant effects on stock prices. However, EPS is not able to mediate the effect of CR and NPM on stock prices.